Strategi Inovasi Usaha Civitas Akademika STEBIS IGM Melalui Media Informasi Teknologi Berbasis Web - Chandra Satria; Doly Nofiansyah (AKM, 2020)
Campus is an environment that can be a mediator and facilitator in developing the creativity of students as the nation's young generation, and campus academic activities have a role to teach, educate, train, and motivate students to become intelligent, creative, innovative, independent and able to create an opportunity to be able to create a workspace not only for itself but also the environment. Utilization of website-based information technology can deepen and practice their business skills during lectures in college.